(untitled) (Swiss Medical Weekly, 2022)
BACKGROUND: General Consent (GC) allows the further use of health-related data/samples for multiple, unspecified research projects and/or for the collection in databases and biobanks in Switzerland. The application of General Consent in the context of human research is regulated within the scope of the Human Research Act. At the University Hospital Zurich patients are informed about General Consent to which they can agree (GC = yes) or disagree (GC = no) to the use of their routinely collected data/samples in research. In this paper, we investigated the association of demographic and medical factors on a patient’s General Consent choice. METHODS: In this cross-sectional study, we investigated the association of age, gender, number of visits and number of diagnoses on General Consent choice. The study population was stratified by General Consent status group (GC choice: Yes, No, Not issued) and examined by means of descriptive statistics, comparative statistics and a multinomial and logistic regression model. A p-value of 0.001 was determined as significant. RESULTS: The female gender was found to associate with decreased odds in positive General Consent choice (<0.001) whereas age (<0.001) and number of diagnoses (<0.001) were associated with increased odds in positive General Consent choice (reference “GC = no” group). The number of visits (<0.001) as well as the number of diagnoses associated (<0.001) with increased General Consent collection (increase in positive as well as negative General Consent status). CONCLUSION: General Consent is an innovative concept that simultaneously informs patients about human research in accordance with Swiss regulations and promotes research with routinely collected data and biological samples in an era with large information repositories. Our results show that medical and demographic factors may influence a patient’s choice. Therefore, approaching these populations and taking additional care to adequately inform and ensure ethical conformity and behaviour is essential. Flexible communication channels may help us reach this goal.